Market admissibility of products processed by agricultural producer groups - Baum, Mikołaj (Przegląd Prawa Rolnego, 2021)
The aim of the article was an attempt to answer the question whether, in the light of the current provisions of EU law and Polish law, it is possible for recognised groups of agricultural producers to market products supplied by their members as well as entities from outside the group. This issue has not been addressed in the literature but it is of a significant practical value. The processing of agricultural products by groups recognised as such pursuant to the Act on agricultural producer groups and their associations has a direct impact on the assessment whether these groups have satisfied the conditions for recognition, which means whether they will retain or lose this status and, therefore the privileges related to it in the form of financial aid from the EU funds, tax exemptions or subsidies to preferential credits. The primary and secondary European Union law and regulations concerning financial aid from EU funds, as well as the relevant judgment of the Court of Justice in the matter in question have been analysed with a conclusion leading to an affirmative answer to the question posed.